Pengaruh Kompetensi Ekonomi Syariah Terhadap Keputusan Bertransaksi Menggunakan Produk Perbankan Syariah - Amin, Arwani (Fakultas Hukum dan Ekonomi Syariah Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2020)
This research was a field research, using quantitative descriptive method; method of data collection was done by observation and questionnaires. Regarding the influence of the Islamic economic competence to the decision to trade using Islamic banking products, samples were taken for this researchto support the implementation of a number of 110 respondents from the study program of Economic Sharia Higher School Islamic Segeran Pangeran Dharma Kusuma Indramayu, and from the number of respondents were given a questionnaire to be answered. Data analysis technique used was to use a statistical technique that is simple correlation technique with the technique Product Moment Correlation analysis using SPSS 15.00 version. The results of this research indicated that the correlation between the Islamic economic competence with the decision to transact in Islamic banks was 0, 915. Based on the interpretation of the correlation coefficient r value, so 0.915 including the level of relations